Dose–response effect of fluoride dentifrice on remineralisation and further demineralisation of erosive lesions: A randomised in situ clinical study. Issue 7 (July 2015) - Creeth, J.E.; Kelly, S.A.; Martinez-Mier, E.A.; Hara, A.T.; Bosma, M.L.; Butler, A.; Lynch, R.J.M.; Zero, D.T.
Abstract Objective The objective was to evaluate the ability of fluoride in a conventional, non-specialised sodium fluoride–silica dentifrice to promote tooth remineralisation and enamel fluoride uptake (EFU), and assess the resistance of the newly formed mineral to attack by dietary acid, across the concentration range used in mass-market dentifrices. Methods Subjects wore a palatal appliance containing eight polished bovine enamel specimens, each including an early erosive lesion. In a randomised full-crossover sequence, 62 healthy subjects were treated with dentifrices containing four different fluoride concentrations: no fluoride; 250 ppm, 1150 ppm and 1426 ppm fluoride. At each treatment visit, under supervision, subjects brushed with 1.5 g dentifrice and rinsed once while wearing the appliance; the appliance was removed after a 4-h remineralisation period and effects on the enamel specimens determined. The primary efficacy variable was surface microhardness recovery (SMHR); others included EFU, relative erosion resistance (RER) and comparative erosion resistance. Results Highly significant linear and, with the exception of SMHR, quadratic dose–response relationships were observed between all efficacy variables and fluoride concentration. For SMHR, EFU and RER, values for the different fluoride concentrations were statistically resolved from one another, with the exception of the two highest fluoride concentrations. The degree of remineralisation and the acid resistance of enamel after treatment were closely related to EFU. Conclusion After a single brushing, conventional non-specialised sodium fluoride–silica dentifrices promoted remineralisation of early enamel lesions, and imparted increased acid-resistance to the enamel surface, in a dose-dependent manner at least up to 1500 ppm fluoride. Clinical significance Enamel erosive tissue loss is an increasing concern, associated with modern diets. This study demonstrated that sodium fluoride, in a conventional non-specialised dentifrice formulation, can promote repair of the earliest stages of enamel erosion after a single application, in a dose-dependent fashion across the fluoride concentration range used in mass-market dentifrices. This study is registered in the GlaxoSmithKline Study Register (ID RH01299), available at: www.gsk-clinicalstudyregister.com/study/RH01299.